A Critical Review of the Implementation of the Seveso III Directive in the Framework of Land-Use Planning: A Comparative Study of Greece, Cyprus, and Slovakia - Ioannis Pissourios; Georgia Gemenetzi; Milan Husár (Land)
This research critically examines the integration of the Seveso III Directive into spatial planning, with a focus on land-use policies in Greece, Cyprus, and Slovakia. It specifically focuses on Article 13, which aims to limit the impact of industrial accidents on human health and the environment through land-use and other relevant policies across four key dimensions: (a) land-use planning, (b) development control, (c) mitigation of existing Major Accident Hazards (MAHs), and (d) consultation procedures. The analysis includes the legal, administrative, and regulatory frameworks of each country, enriched with empirical data and case studies focusing on upper-tier oil and gas refineries. The findings reveal distinct procedural and decision-making approaches among the three countries, closely tied to their respective spatial planning systems and traditions. It also highlights weaknesses and best practices within these diverse planning systems, potentially informing initiatives aimed at establishing a more comprehensive institutional and operational framework for MAH protection.